Quality Gap in Child Care under One Year Using the Servqual Model in Sanandaj Comprehensive Health Centers - Gholipour, Rahil; Shahoei, Roonak; Ghade Khani, Golbahar (Advances in Nursing & Midwifery, 2021)
Abstract Introduction: Childhood has a significant impact on human growth and development. So that children who receive inappropriate care during the first years of life have lower intelligence and less compelling power, become sicker and prolong their illness. To this end, the provision, maintenance and promotion of the health of children under one year is a special status as a vulnerable group in health services. The aim of this study was to determine the quality of care for children under one year using the SERVQUAL model in Sanandaj comprehensive health centers in 2018. Methods: In this descriptive-analytical study, 384 children under one year old who referred to Sanandaj comprehensive health centers were selected by stratified random sampling. Data collection was done using SERVQUAL questionnaire (service quality). Data were analyzed by SPSS-23 software using descriptive statistics, t-test and ANOVA. Results: The results of this study showed that in all aspects of service quality there was a negative gap, then the responsiveness dimension had the highest quality gap and then the assurance dimension had the least quality gap and in all dimensions the average customer expectations were higher than their average perceptions. Conclusions: Given the negative gap in the five dimensions of service quality and high expectations of perception in all dimensions, the needs and expectations of service recipients need to be taken into account in order to reduce the service quality gap.